Impact of Retributive Taxes for Spills Control in Colombia (2017)
This article discusses the ability of traditional econometric estimates of the impact of the retributive taxes as an instrument for spill control in Colombia. For this purpose the effect of fees on pollution is estimated based on two strategies that differ in the type of information that is used as a treatment variable. The first estimate uses a panel data set resulting from the implementation of the retributive taxes in CORNARE's jurisdiction during the period 2011-2014. In this first evaluation the price of the pollution is the rate that charges the environmental authority. In the second case the information comes from a survey applied to companies with spills in the city of Bogotá during the year 2014. For this case the treatment variable is the price perceived by the polluting agents. It was found that the first strategy underestimates the effect of fees because it does not capture the heterogeneous effect of price to pollution and this generates biased and inconsistent estimators of its impact.